ChemInform Abstract: Crystal Structure and Spectroscopic Properties of Garnet‐Type Li7La3Hf2O12:Eu3+. Issue 45 (October 2016) - Leonidov, Ivan I.; Baklanova, Yana V.; Maksimova, Lidiya G.; Tyutyunnik, Alexander P.; Akashev, Lev A.; Vovkotrub, Emma G.; Denisova, Tatyana A.; Zubkov, Vladimir G.
Abstract: A series of polycrystalline Li7 La3‐x Eux Hf2 O12 (x = 0.05—0.20) is prepared by calcination of a mixture of Li2 CO3, La2 O3, Eu2 O3, and HfO2 using a 10 wt% Li excess (Al2 O3 crucible, 1.